RNase A in (Xeno)Transplantation. (March 2014) - Kleinert, Eike; Reichart, Bruno; Mayr, Tanja; Abicht, Jan‐Michael; Brenner, Paolo; Hagl, Christian; Langenmayer, Martin; Wanke, Ruediger; Deindl, Elisabeth; Guethoff, Sonja
<x xml:space="preserve">Abstract</x> Background Cell injury, particularly as consequence of ischemia/reperfusion or acute rejection after (xeno)transplantation, leads to release of intracellular components like RNA. Extracellular RNA, (i) causes edema as a result of increasing permeability of blood vessels [1], (ii) is described as a procoagulation factor by activation of the contact phase system leading to thrombus formation and vessel occlusion [2], and (iii) promotes leukocyte recruitment to the vascular system by mobilising proinflammatory cytokines [3], and thus, triggers immune response. In rodent models of stroke and thrombosis, treatment with counteracting RNase A, a ribonuclease that specifically degrades single‐stranded RNA, was shown to result in less edema formation and vessel occlusion [4]. In search of additive drugs to protect (xeno)grafts from dysfunction, we investigated if treatment with RNase A in a rat model of heterotopic heart transplantation results in less edema and less coronary occlusion, and, therefore, in improved graft survival. Methods Brown Norway rat cardiac allografts were transplanted into the abdomen of Lewis rats after perfusion with Bretschneider cardioplegic solution. Microvascular technique for aorto‐aortic anastomosis and pulmonary artery to inferior vena cava anastomosis (Langendorff) was used. Recipients were intravenously treated directly before transplantation and every other day with RNase A (50 μg/kg) or vehicle (saline, n = 6 in each group). In addition, in six cases the donor graft was perfused with Bretschneider solution containing RNase A (8 μg in 10 ml), and afterwards transplanted into RNase A treated recipients. The primary end point of the study was graft survival, which was determined by daily examination of the graft function by palpation and in case of inconclusiveness by echocardiography. A tolerance study was performed treating animals daily with 50 μg/kg of RNase A, with 1, 000 μg/kg of RNase A, or vehicle, respectively, for 28 days (n = 3 in each group). All explanted hearts were collected for histological evaluation. Results Mean graft survival was 6.5 ± 0.55 day (range 6–7 day) in vehicle treated animals vs. 10.2 ± 1.0 day (range 9–11 day) in RNase A treated animals (P = 0.002). Directly after explantation donor grafts had a mean weight of 0.94 ± 0.03 g (range 0.89–0.98 g). After been rejected, donor graft weight increased to 2.06 ± 0.52 g (range 1.59–2.77 g) in vehicle treated recipients, in contrast to 1.28 ± 0.27 g (1.05–1.61 g) in RNase A treated recipients (P = 0.017). No supplemental benefit was observed by additive using of RNase A in Bretschneider solution (graft survival 9.50 ± 1.52 day, graft weight 1.38 ± 0.15 g) compared to single treatment of the recipient (graft survival P = 0.394, graft weight P = 0.589). Tolerance studies showed neither macroscopic nor histological differences compared to saline treated animals. Outlook: Further histological analyses will help to clarify if RNase A will keep the promise to reduce edema formation even in the field of transplantation, as suggested by the significant less graft weight in RNase A treated recipients. Moreover, we will investigate, if RNase A prevents leukocyte recruitment in the context of rejection reaction. Therefore, grafts of RNase A treated and untreated rats will be explanted on day 4 after transplantation. Conclusions RNase A significantly improved graft survival. On the basis of these sweeping results, however, we suppose that RNase A could be an important adjuvant drug not only in allotransplantation but even in xenotransplantation. References [1] Fischer S, Gerriets T, Wessels C, et al. Extracellular RNA mediates endothelial‐cell permeability via vascular endothelial growth factor. Blood 2007; 110(7): 2457–2465. [2] Kannemeier C, Shibamiya A, Nakazawa F, et al. Extracellular RNA constitutes a natural procoagulant cofactor in blood coagulation. Proc Natl Acad Sci U S A 2007; 104(15): 6388–6393. [3] Fischer S, Grantzow T, Pagel JI, et al. Extracellular RNA promotes leukocyte recruitment in the vascular system by mobilising proinflammatory cytokines. Thromb Haemost. 2012; 108(4): 730–741. [4] Walberer M, Tschernatsch M, Fischer S, et al. RNase therapy assessed by magnetic resonance imaging reduces cerebral edema and infarction size in acute stroke. Curr Neurovasc Res. 2009; 6(1): 12–19.